Towards the cosmetic application of Passiflora coccinea (Aubl.): antioxidant activity and photo protective capacity of the methanolic and glycolic leaf extracts (Brazilian Journal of Pharmaceutical Sciences, 2020)
The present study aimed at the evaluation of Passiflora coccinea (Aubl.) antioxidant and photo protective in vitro activities, looking forward to their application as antiaging or sunscreen agents in cosmetic formulations. Methanolic and glycolic leaf extracts were prepared by three methods: ultrasound assisted extraction (UAE, 30 min.), maceration at room temperature (72 h) and maceration at 30 ºC (72 h). The antioxidant activities of the extracts were measured by DPPH and ORAC-FL assays and they were incorporated into a cosmetic emulsion to have their sun protection factor (SPF) measured spectrophotometricaly. The antioxidant activity of the emulsions were measured by DPPH and ORAC as well. C-glycosyl-flavones were identified in the extracts by ESI-MS/MS, in comparision with standards. The UAE methanolic extract and the maceration at 30 °C glycolic extract were submmited to HPLC-DAD analysis and isovitexin was quantifyed in both by a validated method. The methanolic extract antioxidant activity was independent of the extraction method, higher than reported for other species of Passiflora and detectable when incorporated into the emulsion formulation. Maceration at 30o C was the most suitable method for glycolic extraction and its antioxidant activity was lower than the value presented by the methanolic extracts. None of the extracts exhibited a SPF value. Isovitexin in the UAE methanolic extract was 12.67 times higher than the most active glycolic extract, aside of their similar chromatographic profiles. Although a SPF value was not detected, the results indicate that P. coccinea can be a potential new source of antioxidants for topical antiaging formulations.